P2.119 The Prevalence of Hearing Sensitivity Among HIV-Seropositive and HIV-Seronegative Men and Women. (13th July 2013) - Plankey, M W; Hoffman, H J; Springer, G; Cox, C; Young, M A; Margolick, J B; Torre, P
Abstract : Background: We measured the prevalence of hearing sensitivity among HIV+ and HIV- men and women and identified associated risks co-factors. Methods: Audiometric testing was conducted among 262 men [median age 54.7 years; 117 (44.7% HIV+; median (25th, 75th): nadir CD4+: 296 (191, 400); viral load (VL): 40 (40.40))] from the Baltimore-DC site of the Multicenter AIDS Cohort Study and 134 women [median age 45.2 years; 105 (78.4% HIV+; median (25th, 75th): nadir CD4+: 249 (92, 367); VL: 80 (48, 1270))] from the DC site of the Women's Interagency HIV Study. Pure-tone hearing thresholds were obtained at 500, 1000, 2000, and 4000 Hz and HL was defined as a pure tone average (PTA) ≥ 20 dB hearing level in either ear. A linear mixed model with a random-subjects effect was used to account for two repeated measurements (one per ear) adjusted for age, gender, race, HIV status, and noise exposure. The HIV+ model included nadir CD4+, peak CD8+, VL, ever having AIDS, ever monotherapy (MT), ever combination therapy (CT) and ever HAART use. Results: 84 (95.2% men, 4.8% women) HIV- and 90 (65.6% men, 34.4% women) HIV+ participants had HL in the poorer ear. Age was a statistically significant risk factor of HL, however HIV status and noise exposure were not. In the HIV+ model, nadir CD4+, peak CD8+, VL, ever having AIDS, and MT were not statistically significantly associated with HL. Although there was a higher PTA and a lower PTA with ever CT and HAART use neither was significantly associated with HL. Conclusions: We found no impact of HIV status or treatment variables on HL. HIV-infected individuals who used HAART had a lower PTA, an indicator of better hearing sensitivity. However, due to cross-sectional design of this study, it is not known whether HAART use protects hearing sensitivity.